Bacteriocin-like protein produced Brevibacillus laterosporus that can inhibit the growth of drug resistant bacteria - Monthon Lertcanawanichakul; Kittisak Chawawisit (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2020)
This minireview contains a compendium of bacteriocin or bacteriocin-like proteins produced from Brevibacillus laterosporus that can inhibit the growth of drug resistant bacteria. A good number of bacterial secondary metabolites/ bacteriocin/ bacteriocin-like proteins are reported to have anti-drug resistant bacteria activity or anti-cancer activity comparable to the existing chemical synthesis antimicrobial drugs or sometimes even better. Information regarding the mode of action of bacteriocin leads to insight into their activity relationship and potency. A further well defined strategy is required to exploit these active molecules used as anti-drug resistant bacteria drugs.